Synergistic Coupling of Hierarchical Heterostructured Ni3P/Ni/VN Microflower Electrocatalyst for Enhanced Hydrogen Evolution Reaction. Issue 4 (26th January 2023) - Fu, Changle; Feng, Liangliang; Yin, Hongyan; Li, Yuhang; Li, Guodong; Feng, Yongqiang; Cao, Liyun; Huang, Jianfeng; Liu, Yipu
Abstract: The exploration of economical and highly efficient electrocatalysts for hydrogen evolution reaction (HER) is paramount for the development of sustainable hydrogen economy. Herein, a novel three‐dimensional (3D) hierarchical microflower electrocatalyst comprised of N‐doped carbon‐armored Ni3 P/Ni/VN heterogeneous nanoparticles (Ni3 P/Ni/VN@NC) is developed by combining a hydrothermal method with in‐situ carbonization‐phosphating strategy. The unique robust hierarchical structure derived from 3D NiV layered double hydroxide (NiV‐LDH) skeleton as precursor provides multidimensional mass and charge transport channels as well as numerous active sites for HER, leading to the improved HER activity. More importantly, the possible electron transfer route of Ni3 P→Ni→VN is demonstrated due to the charge pumping capability of VN during interfacial electron intercoupling among the tri‐component, which endows Ni3 P/Ni/VN with the favorable absorption of hydrogen‐intermediates and thus upgraded HER kinetics over such heterostructure. The resulting Ni3 P/Ni/VN@NC catalyst exhibits extremely low overpotentials of 81 mV and 134 mV to deliver a current density of 10 mA cm −2 without iR ‐compensation in alkaline and acidic media, respectively, and maintains continuous operation for over 90 h. This work enlightens the rational design of hierarchical multi‐component heterostructured catalysts for efficient hydrogen production. Abstract : Hierarchized Microflowers for Hydrogen Evoluation Reaction : A novel tactic of synergetic electronic coupling is successfully developed for rationally engineering hierarchical heterostructured electrocatalyst towards hydrogen evolution reaction.